METHODOLOGICAL APPROACHES TO THE DEVELOPMENT OF THE INNOVATIVE POTENTIAL OF SCHOOL TEACHERS - Dildora Mashrabjonovna Khakimova (International Scientific and Current Research Conferences, 2023)
this article scientifically substantiates systematic, synergistic, active, axiological, acmeological approaches to the development of innovative potential of school teachers.